Repeat assessment of examination signs among children in Malawi with fast-breathing pneumonia. Issue 2 (26th May 2020) - Lenahan, Jennifer L.; Nkwopara, Evangelyn; Phiri, Melda; Mvalo, Tisungane; Couasnon, Mari T.; Turner, Kali; Ndamala, Chifundo; McCollum, Eric D.; May, Susanne; Ginsburg, Amy Sarah
Background: As part of a randomised controlled trial of treatment with placebo versus 3 days of amoxicillin for nonsevere fast-breathing pneumonia among Malawian children aged 2–59 months, a subset of children was hospitalised for observation. We sought to characterise the progression of fast-breathing pneumonia among children undergoing repeat assessments to better understand which children do and do not deteriorate. Methods: Vital signs and physical examination findings, including respiratory rate, arterial oxygen saturation measured by pulse oximetry ( S pO2 ), chest indrawing and temperature were assessed every 3 h for the duration of hospitalisation. Children were assessed for treatment failure during study visits on days 1, 2, 3 and 4. Results: Hospital monitoring data from 436 children were included. While no children had S pO2 90–93% at baseline, 7.4% (16 of 215) of children receiving amoxicillin and 9.5% (21 of 221) receiving placebo developed S pO2 90–93% during monitoring. Similarly, no children had chest indrawing at enrolment, but 6.6% (14 of 215) in the amoxicillin group and 7.2% (16 of 221) in the placebo group went on to develop chest indrawing during hospitalisation. Conclusion: Repeat monitoring of children with fast-breathing pneumonia identified vital and physical examination signs not present at baseline, including S pO2 90–93% and chest indrawing. This information may support providers and policymakers in developing guidance for care of children with nonsevere pneumonia. This study characterised the progression of fast-breathing pneumonia among children in Malawi. Repeat monitoring of children identified vital and physical exam signs not present at baseline, including oxygen saturation of 90–93% and chest indrawing. http://bit.ly/2vUlckS